Socialization of Higher Education Promotion Media in Bogor Regency - Saparudin; Ali Alamsyah Kusumadinata (Indonesian Journal of Advanced Social Works, 2023)
Promotional media is one of the tools used to communicate in building perspective. The purpose of the media is to develop larger units and be glimpsed by consumers or clients. The media developed are diverse so that they can reach a wider client. The purpose of this service research is to map the media that has been socialized in the form of student admission promotion. This research method uses qualitative which is part of a method that develops descriptive interpretations in accordance with the activities carried out during promotions held in 2022. The results of this analysis show the use of socialization in the form of personal selling, mass selling, sales promotion, public relations, and direct marketing. In addition, socialization techniques are carried out directly and media. This is to support the level of information exposure to clients and attract consumers to participate in joining the university.